Curcumin-loaded nanoscale coordination polymers for ROS scavenging and anti-inflammatory therapy in atherosclerosis - Song Ding; Wenyi Xu; Xueliang Liu; Zhinan Wu; Xinjie He; Yue Huang; Jiyuan Chen; Wei Yao; Huayuan Zhou; Yu Yang; Jun Pu (Materials Today Bio, 2025)
The progression of atherosclerosis (AS) is marked by escalating chronic inflammation and oxidative stress within the arterial wall, which heightens the risk of plaque rupture and subsequent acute ischemic cardiovascular and cerebrovascular events. Conventional anti-inflammatory and antioxidant therapies, however, are often limited by modest efficacy and potential side effects. Here, we synthesized iron-curcumin coordination polymers (Fe-Cur CPs) coordinated by trivalent iron ions and the natural product curcumin (Cur). These Fe-Cur CPs effectively scavenged excessive reactive oxygen species (ROS) in endothelial cells and macrophages, significantly reduced monocyte adhesion to activated endothelial cells, and attenuated the production of inflammatory factors by macrophages, thereby demonstrating potent antioxidant and anti-inflammatory properties. Additionally, they inhibited foam cell formation. In atherosclerotic ApoE−/− mice, intravenous administration of Fe-Cur CPs significantly reduced plaque burden. Furthermore, these nanoparticles mitigated macrophage aggregation within plaques, effectively inhibited ROS levels and inflammatory cytokine production, enhanced collagen deposition and α-smooth muscle actin (α-SMA) levels, and downregulated matrix metalloproteinase 9 (MMP9) levels, thereby collectively contributing to plaque stabilization. This study proposed a safe and efficient self-assembly strategy for constructing multifunctional coordination polymers that possessed drug-delivery capabilities. These nanoparticles can synergistically modulate multiple risk factors in the atherosclerotic plaque microenvironment, thereby offering a promising therapeutic approach for the treatment of AS.